2020
DOI: 10.21037/tau-20-629
|View full text |Cite
|
Sign up to set email alerts
|

Safety of two common laparoscopic inguinal herniorrhaphy approaches: an updated systematic review with meta-analysis of randomized clinical trials

Abstract: Background: Previous evidence indicated that total extraperitoneal (TEP) and transabdominal preperitoneal (TAPP) are advantageous in efficacy of inguinal herniorrhaphy. Therefore, our aim in this study was to evaluate the association of the two laparoscopic approaches on safety of inguinal herniorrhaphy.Methods: In this update study, we searched the Cochrane Library, EMBASE, PubMed, Scopus, and Web of Science and identified randomized clinical trials comparing complications in TEP and TAPP herniorrhaphy.We mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…TAPP operation demonstrated only one advantage over Lichtenstein operation with significantly less chronic inguinal pain postoperatively [36]. TAPP was associated with a lower seroma rate, and TEP was associated with a lower edema rate according to a meta-analysis [37]. There was less early pain and fewer analgesics after TEP repair, compared to Lichtenstein repair with similar infection rates in this Randomized Controlled Trial (RCT) [38].…”
Section: Complications Of Laparoscopic Inguinal Hernia Repairmentioning
confidence: 76%
“…TAPP operation demonstrated only one advantage over Lichtenstein operation with significantly less chronic inguinal pain postoperatively [36]. TAPP was associated with a lower seroma rate, and TEP was associated with a lower edema rate according to a meta-analysis [37]. There was less early pain and fewer analgesics after TEP repair, compared to Lichtenstein repair with similar infection rates in this Randomized Controlled Trial (RCT) [38].…”
Section: Complications Of Laparoscopic Inguinal Hernia Repairmentioning
confidence: 76%
“…Başka bir metaanalizde TEP onarımı ile Lichtenstein onarımı karşılaştırılmış ve ameliyat sonrası komplikasyonlar ve tekrar onarım gereksinimi açısından TEP yöntemi daha avantajlı bulunmuştur; ancak aynı avantajın TAPP için geçerli olmadığı gösterilmiştir 15 . TAPP tekniğinde peritoneal kavitenin eksplore edilmesi ve her iki inguinal bölgenin de muayene edilebilmesi avantajı vardır 7,16 . TEP tekniği, karın boşluğuna girmeden miyopektineal orifislerin araştırılmasına, fıtık kesesinin diseksiyon ve redüksiyonuna ve yamanın yerleştirilmesine olanak sağlar 17,18 .…”
Section: Discussionunclassified
“…The main problem with post-operative seroma is that they may be mistaken for recurrences and there are reports where the correct diagnosis being made only after groin exploration 9 . Recently in 2020, safety of laparoscopic inguinal herniorrhaphy approaches (TAPP, TEP) was reviewed in a meta-analysis of randomized clinical trials by Hung et al and it was found that both TEP and TAPP have their own advantages in inguinal hernia repair but TAPP was associated with a lower seroma rate 11 .…”
Section: Discussionmentioning
confidence: 99%